Broadening horizons: the role of ferroptosis in cancer - Chen, Xin; Kang, Rui; Kroemer, Guido; Tang, Daolin (Nature reviews. Clinical oncology, 2021)
The discovery of regulated cell death processes has enabled advances in cancer treatment. In the past decade, ferroptosis, an iron-dependent form of regulated cell death driven by excessive lipid peroxidation, has been implicated in the development and therapeutic responses of various types of tumours. Experimental reagents (such as erastin and RSL3), approved drugs (for example, sorafenib, sulfasalazine, statins and artemisinin), ionizing radiation and cytokines (such as IFNγ and TGFβ1) can induce ferroptosis and suppress tumour growth. However, ferroptotic damage can trigger inflammation-associated immunosuppression in the tumour microenvironment, thus favouring tumour growth. The extent to which ferroptosis affects tumour biology is unclear, although several studies have found important correlations between mutations in cancer-relevant genes (for example, RAS and TP53), in genes encoding proteins involved in stress response pathways (such as NFE2L2 signalling, autophagy and hypoxia) and the epithelial-to-mesenchymal transition, and responses to treatments that activate ferroptosis. Herein, we present the key molecular mechanisms of ferroptosis, describe the crosstalk between ferroptosis and tumour-associated signalling pathways, and discuss the potential applications of ferroptosis in the context of systemic therapy, radiotherapy and immunotherapy.